Design, Application and Comparison of Passive Filters for Three-Phase Grid-Connected Renewable Energy Systems - Hojabri, Mojgan; Hojabri, Mehrdad (2015)
Second and third-order passive filters (LC and LCL) are interesting filters to use for grid-connected PWM inverters. Because of the stability problems of these filters around resonance frequency, series and damping resistor can be add to an LCL filter. However, the resistor value has impact on the filter respond, voltage and current harmonic distortion and filter power loss. In this paper, the mathematic characteristics of LC, LCL filter, series and parallel damping LCL filters will be described with their design to apply in 3-phase PV grid-connected inverter. And, simulations have down to validate the theoretical analysis of the filters on filter performance, power quality and filter power loss for 3-phase grid-connected renewable energy system application.